FINANCIAL-ECONOMICAL ENTERPRISE SECURITY STRATEGY FORMING IN THE TERMS OF UNCONFORMITY - Mykhayliv , G.V. (The actual problems of regional economy development, 2016)
Theoretical points as for definition of “financial-economical security” have been researched and summing up. The present attitude were analyzed as for the financial-economical enterprise security forming in the terms of unconformity and system attitude necessity stipulated for strategy system management by a financial-economical enterprise security. JEL: M 20